Peran Guru dalam Pengembangan Kurikulum dan Pembelajaran - surahmat, sriyeni (Prodi PGMI STAI Sabili Bandung, 2025)
This study aims to determine the role of teachers in curriculum development and implementation of the learning process. This research uses a qualitative method of literature study approach, where researchers look for various written references, such as journals with books that are considered relevant. In the education system, the curriculum is the most important component. It functions as a dynamic teaching-learning device, therefore, it needs to be evaluated and refined on an ongoing basis to be in tune with the dynamics that occur in society. The role of teachers in curriculum development can vary depending on the model used, such as centralization, decentralization, or a combination of both. In general, there are several developments that must be prioritized by teachers, as implementers, adapters, developers and researchers. In addition, teachers play a very important role in learning because of the reciprocal relationship, which is an important condition for learning. The role of the teacher in this case is not only focused on the transfer of knowledge, but also on the transfer of values. In conclusion, the role of teachers in curriculum development is very influential on their success in the process of implementing learning, and this is the key to obtaining the educational goals that have been formalized by the curriculum.